Relationship between religiosity, shame and guilt among Malaysian Muslims youth - Sawai, Rezki Perdani; Mohd Noah, Sidek; Krauss, Steven Eric; Sulaiman, Mashitah; Sawai, Joki Perdani; Mohd Safien, A'isyah (Human Resource Management Academic Research Society, 2017)
According to prominent theories of social control such as social bonding theory, religion has shown to be an influential factor of social control in building an ethical and moral society. Among the core religious teachings in construction of one’s self is the person’s shame and guilt emotions. It is believed that when a person is conscious about religion, they are more likely to experience feelings of shame and guilty after engaging in behaviors deemed sinful. This article aims to study the relationships between religiosity and moral emotions (shame and guilt) among Malay youth in Malaysia. A quantitative survey was conducted from June to September 2015 in Klang Valley which was involved 250 respondents (73 males and 177 females). The study set out to examine the relationships between religiosity and moral emotions and to examine whether there are differences in moral emotions (shame and guilt) by gender. Two measures were used to carry out the study. The Muslim Religiosity Personality Inventory (MRPI) was used to measure religiosity, while Muslim Moral Emotion Inventory (MMEI) was used to measure moral emotions. Overall, the study results showed a positive correlation between in God-consciousness and shame and guilt, supporting the study hypothesis.